Effects of stocking density and water conditioners on yolk‐sac larvae of two marine finfish during simulated air transport. (27th December 2013) - Stuart, Kevin; Losordo, Malia; Olin, Paul; Drawbridge, Mark
Abstract As marine finfish aquaculture expands, there is an increasing interest in the ability to ship early life stages from breeding centres to hatcheries so that each hatchery does not have to maintain its own broodstock. Here, we conducted 24 h air‐shipping simulations with yolk‐sac larvae of California yellowtail (CYT; Seriola lalandi) and white seabass (WSB; Atractoscion nobilis) to help fill in the informational gaps for shipping marine fish larvae. We examined the effects of a pH buffer on water quality, post‐shipping larval survival and subsequent survival to first feeding at larval densities of 1000, 3000, 6000 and 9000 larvae L−1. The pH buffer, 8.3 Trizma®, was tested at varying concentrations of zero (NT = 0.00 g L−1), low (LT = 0.75 g L−1), medium (MT = 1.5 g L−1) and high (HT = 3.0 g L−1). Trials were conducted using replicate 2 L aquarium bags filled with 500 mL of seawater and held in a water bath at 19–20°C. Results showed an interspecific difference in survival at the highest shipping densities under these experimental conditions. Shipping densities up to 6750 CYT larvae L−1 or 3000 WSB larvae L−1 consistently yielded >90% survival immediately after simulated shipment and >85% survival 48 h after the simulations. Furthermore, at these densities, pH was maintained at 8.0 when buffered at 1.5 g L−1. The highest tested densities of 9580 CYT larvae L−1 and 9940 WSB larvae L−1, yielded lower survival 69–79% and 0.0–1.3% respectively after 24 h. Final pH in the high density CYT trials were unsatisfactory (below 7.0), regardless of the buffer concentration; however pH in the WSB high density trials improved with increasing buffer concentration. On the basis of the results from these air‐shipping simulations, we recommend CYT and WSB larvae be shipped in seawater with 1.5 g L−1 Trizma® at densities not greater than 6750 larvae L−1 for CYT and 3000 larvae L−1 for WSB. We believe this represents an important step in improving long distance transport protocols for these species and provides useful guidance in air transport of other economically and ecologically important marine species. Additional research is warranted to compare these simulation results with those from actual air shipments, as we did not account for factors that may vary in flight like temperature and pressure variations, and physical agitation.